ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP MATA KULIAH SISTEM INFORMASI AKUNTANSI (Studi Pada Mahasiswa Akuntansi UNDIP) - Muhammad Revo Hanifan; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to examine what factors can affect the level of understanding of accounting students in accounting information systems courses as one of the studies in accounting science.      The population in this study were accounting students at Diponegoro University who had completed accounting information systems courses. The sample in this study was selected by purposive sampling method. In this study there will be 80 accounting students at Diponegoro University who have met the predetermined criteria. The method used in conducting the analysis is multiple linear analysis.      The results of the research conducted show that the disclosure of teaching styles, learning methods, prior knowledge, critical thinking has a significant influence on the level of understanding of accounting students in accounting information systems courses. Meanwhile teacher support, student interest, and appreciation of accounting information systems do not have a significant effect on the level of understanding of accounting students in accounting information systems courses.